2020
DOI: 10.1002/mgg3.1415
|View full text |Cite
|
Sign up to set email alerts
|

A module of multifactor‐mediated dysfunction guides the molecular typing of coronary heart disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…It should be noted that hyporesponsiveness of the immune system and an anti-inflammatory effects were suggested upon activation of HCAR3 [47,48]. It was also indicated that HCAR3 could be involved in sepsis [49] and coronary heart disease [50]. A single study identified HCAR3 as a potential target in colorectal cancer [51].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that hyporesponsiveness of the immune system and an anti-inflammatory effects were suggested upon activation of HCAR3 [47,48]. It was also indicated that HCAR3 could be involved in sepsis [49] and coronary heart disease [50]. A single study identified HCAR3 as a potential target in colorectal cancer [51].…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin heavy chain 1 (FTH1), a major intracellular iron storage protein, is a substrate of ferroptosis, which emerges to play vital roles in coronary atherosclerotic heart disease [ 7 ]. Li et al have reported that FTH1 is significantly up-regulated in blood samples of coronary atherosclerotic heart disease patients [ 33 ]. HIF1A rs2057482 polymorphism is related to the occurrence of coronary heart disease and some metabolic parameters and cardiovascular risk factors [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a bioinformatics approach, WGCNA was utilized to create a scale-free network according to gene expression profiles [ 13 ]. All genes in a module are groups of genes with similar patterns of expression [ 14 ].…”
Section: Methodsmentioning
confidence: 99%